Characterization of magnesium silicate hydrate (M-S-H). (February 2019) - Bernard, Ellina; Lothenbach, Barbara; Chlique, Christophe; Wyrzykowski, Mateusz; Dauzères, Alexandre; Pochard, Isabelle; Cau-Dit-Coumes, Céline
Abstract: In this study, the structure of synthetic magnesium silicate hydrated phases (M-S-H) and the distribution of water as a function of the Mg/Si ratio were investigated. Different analytical techniques indicated that M-S-H phases are nano-crystallite hydrated phyllosilicates with relatively short coherence length (1.2 nm) and small particle size (>200 m 2 /g). Zeta potential and cations exchange capacity measurements showed a negative surface charge on M-S-H from the deprotonation of the silanol groups. The negative surface charge is compensated by exchangeable magnesium or others cations. Combined analyses were used to characterize the water distribution in M-S-H revealing the following: i) confined water; its amount depends mainly on the relative humidity ii) very confined water (or possibly water coordinated to magnesium), and iii) hydroxyl groups bound to magnesium and to silicon.